Transformational Leadership Drives Achievement Motivation and Enhances Customer Service Quality in Islamic Banking in Bandung - Tini Supartini (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2025)
This study examines the extent to which transformational leadership influences achievement motivation and enhances customer service quality in Islamic banks in Bandung. The research employs a quantitative method using a survey approach, targeting employees working in Islamic banking institutions in the region. Data analysis utilizes structural equation modeling (SEM) with PLS, based on a sample of 100 respondents selected through simple random sampling. The findings reveal a significant impact of transformational leadership on both achievement motivation and customer service quality. This research contributes to the understanding of how effective leadership can drive employee motivation and improve service delivery in the banking sector. The implications of these results suggest that fostering transformational leadership within Islamic banks can lead to higher employee engagement and better customer experiences.